Links of Previously Experienced Unemployment to the Subjective Well-Being of Older Adults in the Baltic States - Kairys, Antanas; Sadauskaitė, Raimonda; Bagdonas, Albinas; Eimontas, Jonas; Pakalniškienė, Vilmantė; Zamalijeva, Olga (Socialinė teorija, empirija, politika ir praktika, 2021)
In this paper, using data obtained from the Survey of Health, Ageing and Retirement in Europe (SHARE), previously experienced unemployment links to the subjective well-being of older adults in the Baltic States are analyzed.One of the global challenges faced by a considerable number of countries is the aging of society. Subjective well-being of older adults and its factors are becoming one of the fundamental issues of the research as older adults are becoming a bigger part of society, and it becomes critical to understand what makes their lives wholesome. According to the life course perspective, human development is a lifelong process, and various events, personal life experiences may shape people and their lives. Therefore, it can be assumed that such a significant event as previously experienced unemployment may be related to the subjective well-being at older ages. Thus, this study aims to analyze the links between previously experienced unemployment and the subjective well-being of life of older adults in the Baltic States.Data obtained from the 7th wave of the Survey of Health, Ageing and Retirement in Europe (SHARE) was used for the analysis (Bergmann et al., 2019; Börsch-Supan, 2020). Two thousand eight hundred five responses of Estonians, 941 of Lithuanians, and 809 of Latvians over the age of 50 were analyzed. The subjective well-being, previously experienced unemployment, socio-demographic, personality, and health factors were analyzed.Research results show that many factors predict the subjective well-being of older adults in the three Baltic States: sociodemographic data can explain around 11% of the variance of the subjective well-being. Income additionally explains 2%, factors related to a person’s health adds 11% to the explanation, personality traits – also 11%, previously experienced unemployment – less than 1%. In the model containing all the factors, the most important predictor was personality trait neuroticism, and the model explained 35% of the variance of the subjective well-being. The subjective well-being was not linked only to gender and living with a partner. By analyzing the links between previously experienced unemployment and subjective well-being, we found that these links are relatively weak, although they remain even when controlling a range of factors of subjective well-being.
Keywords: subjective well-being; unemployment; personality